(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This work studies the poetic and aesthetic interpretation of the harmony of imagery and lyrical hero in the work of the poetess Zulfiya. Zulfiya’s poetry captivates the reader’s heart with its system of artistic images and the uniqueness of the lyrical hero. Her works are able to penetrate the deep layers of the human psyche and awaken emotions. The poetess’s philosophical and intellectual views and the emotional conclusions arising from them lead the reader to thoughts about life, man and existence. Each line of Zulfiya’s lyrics expresses the spirit of the era, the brilliance of dreams and life’s suffering. The work clearly analyzes the poet’s creative style, philosophical views and aesthetic principles.